Analisis keekonomian injeksi surfactant huff and puff di lapangan dandelion menggunakan kontrak gross split - Muhammad Ariyon; Dike Fitriansyah Putra; Claudia Anugerah Putri (EcoNews, 2022)
Indonesia has proven oil reserves of around 3.7 million barrels but production has been declining unwittingly over the last decade as companies rely solely on the Old Oil Field. PT. SPR Langgak is one of the companies that own the Old Oil Field so it is necessary to develop it to increase production in the Dandelion Field. One of them is the surfactant huff and puff method. However, because surfactants are expensive and this work depends on the economy and oil prices, there need to be more attractive investment options. There is a new investment option prepared by the Government, namely the Gross Split PSC cooperation contract based on Ministerial Regulation no. 52/2017. This study aims to analyze the economic feasibility of Huff and Puff Surfactant Injection using the gross split contract. From the calculation results, the Huff and Puff Surfactant Injection Project at the Dandelion Field is economically feasible to do because it has a large and positive NPV value (NPV = 7,862 M US$, an IRR value greater than the MARR 15% (IRR = 214% and POT value are less than the project life or faster (POT = 1.62 months). Based on the sensitivity analysis, the huff & puff surfactant injection job will be more profitable if the oil price and large oil production. On the other hand, the operating cost is better if the value is small. The lowest limit for oil prices is 28.1 US$/bbl.